Three new cribrimorph bryozoans (order Cheilostomatida) from the early Miocene of Argentina, with a discussion on spinocystal shield morphologies. (May 2021) - López-Gappa, Juan; Pérez, Leandro M.; Almeida, Ana C.S.; Iturra, Débora; Gordon, Dennis P.; Vieira, Leandro M.
Abstract: Bryozoans with calcified frontal shields formed by the fusion of costae, collectively constituting a spinocyst, are traditionally assigned to the family Cribrilinidae. Today, this family is regarded as nonmonophyletic. In the Argentine Cenozoic, cribrilinids were until recently represented by only two fossil species from the Paleocene of Patagonia. This study describes the first fossil representatives of Jolietina and Parafigularia : J. victoria n. sp. and P. pigafettai n. sp., respectively. A fossil species of Figularia, F. elcanoi n. sp., is also described. The material comes from the early Miocene of the Monte León and Chenque formations (Patagonia, Argentina). For comparison, we also provide redescriptions of the remaining extant species of Jolietina : J. latimarginata (Busk, 1884 ) and J. pulchra Canu and Bassler, 1928a . The systematic position of some species previously assigned to Figularia is here discussed. Costafigularia n. gen. is erected, with Figularia pulcherrima Tilbrook, Hayward, and Gordon, 2001 as type species. Two species previously assigned to Figularia are here transferred to Costafigularia, resulting in C. jucunda n. comb. and C. tahitiensis n. comb. One species of Figularia is reassigned to Vitrimurella, resulting in V. ampla n. comb. The family Vitrimurellidae is here reassigned to the superfamily Cribrilinoidea. The subgenus Juxtacribrilina is elevated to genus rank. Inferusia is regarded as a subjective synonym of Parafigularia . Parafigularia darwini Moyano, 2011 is synonymized with I. taylori Kuklinski and Barnes, 2009, resulting in Parafigularia taylori n. comb. Morphological data suggest that these genera comprise different lineages, and a discussion on the disparities among cribrilinid (sensu lato) spinocysts is provided. UUID: http://zoobank.org/215957d3-064b-47e2-9090-d0309f6c9cd8